Electricity production from municipal solid waste using microbial fuel cells with municipal solid waste incinerator bottom ash as electrode plate. (September 2022) - Chen, Chih-Kuei; Pai, Tzu-Yi; Lin, Kae-Long; Ganesan, Sivarasan; Ponnusamy, Vinoth Kumar; Lo, Fang-Chen; Chiu, Hsun-Ying; Banks, Charles J.; Lo, Huang-Mu
Abstract: Municipal solid waste (MSW) incinerator (MSWI) bottom ash can be used as environmental and energy related materials. This study investigated the effect of electrode plate (EPl) of sintered MSWI bottom ash (SMBA, 1050 °C) and carbon felt (CF) on the electricity production (EPr) of MSW using microbial fuel cells (MFCs). The size of each EPl was 6 cm W × 0.5 cm T × 8 cm H . The electron acceptors (EA) in cathode chamber were O2, O2 + distilled water (DW), KMnO4 and O2 + KMnO4 and with four different EPl collocations. Results showed that maximum power density (PD) ranked the order of KMnO4 + O2 > KMnO4 > DW + O2 > DW with each EPl collocation. Similarly, maximum PD followed the order of CF/CF > CF/SMBA > SMBA/CF > SMBA/SMBA with each of four EA. Results showed that SMBA EPl has potential to be used in the MFCs for the EPr. Graphical abstract: The electricity production in MSW microbial fuel cells. Unlabelled Image Highlights: Sintered MSW incinerator bottom ash (SMBA) as electrode in MFCs was investigated. Power density was affected with different electron acceptors and electrode plates. Power density followed the order of CF/CF > CF/SMBA > SMBA/CF > SMBA/SMBA. SMBA sintered with 1050 °C has potential use for MFCs electrode.